Shedding new light on the generation of the visual chromophore - Palczewski, Krzysztof (Proc Natl Acad Sci U S A, 2020)
The visual phototransduction cascade begins with a cis–trans photoisomerization of a retinylidene chromophore associated with the visual pigments of rod and cone photoreceptors. Visual opsins release their all-trans-retinal chromophore following photoactivation, which necessitates the existence of pathways that produce 11-cis-retinal for continued formation of visual pigments and sustained vision. Proteins in the retinal pigment epithelium (RPE), a cell layer adjacent to the photoreceptor outer segments, form the well-established “dark” regeneration pathway known as the classical visual cycle. This pathway is sufficient to maintain continuous rod function and support cone photoreceptors as well although its throughput has to be augmented by additional mechanism(s) to maintain pigment levels in the face of high rates of photon capture. Recent studies indicate that the classical visual cycle works together with light-dependent processes in both the RPE and neural retina to ensure adequate 11-cis-retinal production under natural illuminances that can span ten orders of magnitude. Further elucidation of the interplay between these complementary systems is fundamental to understanding how cone-mediated vision is sustained in vivo. Here, we describe recent advances in understanding how 11-cis-retinal is synthesized via light-dependent mechanisms.